Effect of adverse childhood experiences on hypothalamic–pituitary–adrenal (HPA) axis function and antidepressant efficacy in untreated first episode patients with major depressive disorder - Yang, Jian Zhong; Kang, Chuan Yuan; Yuan, Jing; Zhang, Yan; Wei, Yu Jun; Xu, Li; Zhou, Fang; Fan, Xinxin (Psychoneuroendocrinology, 2021)
Adverse childhood experiences (ACEs) has been associated not only with an increased vulnerability for stress-related psychiatric disorders but also with distinct alterations of the hypothalamic–pituitary–adrenal (HPA) axis function and the immune system. The aim of this study is to examine differences in the HPA axis between major depressive disorder (MDD) patients with and without ACEs, and to explore differences in efficacy and HPA changes after long term antidepressant treatment between these two groups. A cohort of 803 patients with MDD were recruited. After the determination of cortisol (COR) and adrenocorticotropic hormone (ACTH), Hamilton Rating Scale for Depression (HAMD), Hamilton Rating Scale for Anxiety (HAMA), the Childhood Trauma Questionnaire (CTQ), 403 subjects were recruited for the following treatment study. Finally 330 MDD patients finished the monotherapy treatments of four antidepressants (Fluoxetine, Sertraline, Venlafaxine-extended release (XR), Duloxetine hydrochloride) for 12 weeks. Of 403 patients, 226 (56%) patients reported ACEs. Total score of HAMD in MDD with ACEs were higher than those in MDD without ACEs. There were significant differences for both ACTH and COR between MDD patients with and without ACEs that MDD patients with any types of maltreatment had higher level. Both COR and ACTH was positively and significantly correlated with the total scores of CTQ, HAMD, HAMA. After 12 weeks treatment of antidepressants monotherapy, the mean (SD) changes in HAMD and HAMA total scores was greater in MDD without ACEs than those in MDD with ACEs. At the 12-week end point, response was achieved by 37.2% in the MDD with ACEs group, 59.0% in the MDD without ACEs group respectively, with significant difference. Remission was achieved by 15.2% in the MDD with ACEs group and 32.2% in the MDD without ACEs group, with significant difference. The change in ACTH level in MDD without ACEs was also greater than that in MDD with ACEs, which was positively and significantly correlated with the HAMD total score only in MDD patient without ACEs. Logistic regression analysis showed that the total scores of CTQ, level of COR and ACTH at baseline were significantly associated with the response and remission. These findings indicated that exposure to ACEs for MDD could influence the HPA function and severity of symptoms. ACEs, ACTH and COR could be used as predictors of long term antidepressant treatment, suggested that are poor prognostic signs for antidepressants monotherapy in MDD with ACEs. •Effect of adverse childhood experiences.•Major depressive disorder and hypothalamic–pituitary–adrenal axis.•Predictors of treatment.